2006
DOI: 10.1088/1478-3975/3/4/002
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance fluctuations causing channel noise reduction in stochastic Hodgkin–Huxley systems

Abstract: Voltage-dependent ion channels determine the electric properties of axonal cell membranes. They not only allow the passage of ions through the cell membrane, but also contribute to an additional charging of the cell membrane resulting in the so-called capacitance loading. The switching of the channel gates between an open and a closed configuration is intrinsically related to the movement of gating charge within the cell membrane. At the beginning of an action potential, the transient gating current is opposit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…(7a) replaces Eq. (6) [22]. Remarkably, the nodal membrane size A, which is the same for all nodes, solely influences the intrinsic noise strength.…”
Section: Stochastic Generalization Of the Hodgkin-huxley Modelmentioning
confidence: 99%
“…(7a) replaces Eq. (6) [22]. Remarkably, the nodal membrane size A, which is the same for all nodes, solely influences the intrinsic noise strength.…”
Section: Stochastic Generalization Of the Hodgkin-huxley Modelmentioning
confidence: 99%
“…Spiral waves might serve as emergent population pacemakers, generating periodic activity in non-oscillatory networks without individual cellular pacemakers. The formation, death, and breakup of spiral waves in the mammalian cortex can be simulated using regular and/or small-world networks [8][9][10].In networks using Hodgkin-Huxley model neurons [20], the effects of channel noise [21,22] on spiral waves needs to be studied in detail.Normal signal propagation between neurons in networks with different topologies deeply depends on the collective behavior of neurons. Abnormalities of neurons in one domain can destroy the normal communication between neurons, and neurological disorders can occur when the normal electrical activity of neurons is violated.…”
mentioning
confidence: 99%
“…In networks using Hodgkin-Huxley model neurons [20], the effects of channel noise [21,22] on spiral waves needs to be studied in detail.…”
mentioning
confidence: 99%
“…It is better to study spiral wave dynamics in networks of Hodgkin-Huxley (H-H) neurons than in networks of Hindmarsh-Rose (H-R) neurons [4,5] because the H-R neuron model is a simplified version of the realistic H-H model. Channel noise can change the dynamics of H-H neurons greatly [31,32]. White et al [31] pointed out that the probabilistic gating of voltage-dependent ion channels is a source of electrical 'channel noise' in neurons.…”
mentioning
confidence: 99%
“…White et al [31] pointed out that the probabilistic gating of voltage-dependent ion channels is a source of electrical 'channel noise' in neurons. Schmid et al [32] reported the capacitance fluctuations reducing channel noise in stochastic H-H systems. Fox et al [33] presented the autocorrelation functions of channel noise to estimate the effect of channel noise.…”
mentioning
confidence: 99%